SEBARAN HABITAT LARVA Anopheles spp. DI KELURAHAN TANGKILING KOTA PALANGKA RAYA - Ayunda, Bintang; Jabal, Arif Rahman; Ratnasari, Arini; Augustina, Indria; Nawan (Program Studi Teknologi Laboratorium Medis, 2024)
Malaria cases are still a problem throughout the world, especially in Palangka Raya City. Malaria is still a health problem that causes death, especially in infants, toddlers and pregnant women. This study aims to determine the distribution of Anopheles spp. larvae in Tangkiling Village, Palangka Raya City. This study used a survey method. Anopheles larval habitats were found at five points in Tangkiling Village, with habitats in the form of three puddles, fish ponds and water reservoirs. Each Anopheles habitat is close to residential areas and cattle pens.